Precipitation frequency alters peatland ecosystem structure and CO2 exchange: Contrasting effects on moss, sedge, and shrub communities. (16th February 2018) - Radu, Danielle D.; Duval, Tim P.
Abstract: Climate projections forecast a redistribution of seasonal precipitation for much of the globe into fewer, larger events spaced between longer dry periods, with negligible changes in seasonal rainfall totals. This intensification of the rainfall regime is expected to alter near‐surface water availability, which will affect plant performance and carbon uptake. This could be especially important in peatland systems, where large stores of carbon are tightly coupled to water surpluses limiting decomposition. Here, we examined the role of precipitation frequency on vegetation growth and carbon dioxide (CO2 ) balances for communities dominated by a Sphagnum moss, a sedge, and an ericaceous shrub in a cool temperate poor fen. Field plots and laboratory monoliths received one of three rainfall frequency treatments, ranging from one event every three days to one event every 14 days, while total rain delivered in a two‐week cycle and the entire season to each treatment remained the same. Separating incident rain into fewer but larger events increased vascular cover in all peatland communities: vascular plant cover increased 6× in the moss‐dominated plots, nearly doubled in the sedge plots, and tripled in the shrub plots in Low‐Frequency relative to High‐Frequency treatments. Gross ecosystem productivity was lowest in moss communities receiving low‐frequency rain, but higher in sedge and shrub communities under the same conditions. Net ecosystem exchange followed this pattern: fewer events with longer dry periods increased CO2 flux to the atmosphere from the moss while vascular plant‐dominated communities became more of a sink for CO2 . Results of this study suggest that changes to rainfall frequency already occurring and predicted to continue will lead to increased vascular plant cover in peatlands and will impact their carbon‐sink function. Abstract : We manipulated rainfall frequency over three vegetation communities in a temperate cool fen. Lower frequency events led to increased vascular plant abundance. Additionally, lower frequency rain events led to greater loss of carbon dioxide from moss communities. Conversely, lower frequency rain events led to greater net uptake of carbon dioxide in sedge‐ and shrub‐dominated communities. Our results suggest that intensification of the precipitation regime will lead to increased vascular plant coverage in peatland ecosystems, which could threaten their carbon‐sink function.